MANAJEMEN PROGRAM TAHFIZ DALAM PEMBENTUKAN KARAKTER SANTRI: STUDI DI SEKOLAH MENENGAN PERTAMA PLUS NURUL HIKMAH PAMEKASAN - Ratnawati, Rinta; Fajar Purwoko, Lukman; Abdul Majid; Martinus Pekei; Budi Purwoko (re-JIEM (Research Journal of Islamic Education Management), 2024)
The Tahfiz program is designed systematically, including recruiting qualified teachers, flexible schedule arrangements, and regular evaluations. This study aims to analyze the management of the Tahfiz program to improve the character of students at SMP Plus Nurul Hikmah Pamekasan. The results of the study indicate that the management of the Tahfiz program is carried out through four stages: planning, organizing, implementing, and evaluating. Planning involves program initiation, preparing a structured schedule, and setting realistic memorization targets. Organizing includes teacher selection based on memorization and tajwid qualifications, as well as dividing tasks according to student abilities. The implementation of the program focuses on the formation of student character through memorization of the Qur'an and spiritual values. Evaluation is carried out consistently through daily monitoring and monthly meetings. Supporting factors include adequate facilities, such as a conducive mosque, and intensive guidance from teachers. Inhibiting factors include a lack of discipline and student motivation. Overall, the Tahfiz program plays an important role in improving the character and spirituality of students through organized management and directed implementation